Teachers’ experiences of violence from learners in three high schools in the KwaZulu-Natal Pinetown district - Mcobothi, Siboniso Talent (Stellenbosch : Stellenbosch University, 2025)
Thesis (MEd)--Stellenbosch University, 2025.